Pengembangan Perangkat Pembelajaran Fisika Berbasis Problem Based Learning Untuk Meningkatkan Penguasaan Konsep Fisika Peserta Didik Kelas X SMAN 1 Sakra Timur - Lutfi, Abdul Rasyid; Sahidu, Hairunnisyah; Taufik, Muhammad (Indonesian Journal of STEM Education, 2021)
The aims of this study to develop a product in the form of a learning instruction based on problem based learning that valid, practically, and effective to improving student conceptual understanding .This research is included in Research & Development (R&D). The research location in SMAN 1 Sakra Timur, East Lombok, NTB. The subjects consisted of 26 students. The data analysis technique in this study used SBi to know the validity of learning instructions and N-Gain for effectiveness. The validation results from the experts show that the learning instruction based on problem based learning consisting 27.60 for syllabus, 61.00 for lesson plans, 32.40, student worksheets, 33.60 for concept understanding test instruments are categorized as valid and feasible for use in research.. The observation of teacher show that problem base learning tools are practical in terms of their implementation. And the result of N-Gain for conceptual understanding indicator C1 to C6 is 29.73 that category is low. So the conclusing of development of learning instructions based on problem based learning is valid, practical, and effectives to improve the conceptual understanding.